Growth Performance, Nutrient Digestibility and Ceacal Microbial Population of Weaned Pigs Fed Maize Cob-Cassava Peel Mixture as Partial Replacement for Maize - Daniel Nnadozie Anorue; Oluwafemi Roland Rufus; Agubosi Oluchi Precious (International Journal of Global Sustainable Research, 2024)
This study was carried out to determine the growth performance, nutrient digestibility and ceacal microbial population of weaned pigs fed maize cob-cassava peel mixture as partial replacement for maize. Animals in treatment 1 (T1) were fed 0 % maize cob-cassava peel mixture (CPMCM) while CPMCM was used to replace maize at 10 %, 20 % and 30 % in T2, T3 and T4 respectively. Feed and clean water were offered to pigs throughout the experiment that lasted for 60 days. Results obtained revealed that average daily weight gain, average daily feed intake, feed conversion ratio and mortality were not significantly (P>0.05) influenced by the treatments. Nutrient digestibility of crude protein, crude fibre, ether extracts, dry matter and nitrogen free extract were not significantly (P>0.05) different among the treatment. Microbial population of Escherichia coli and Lactobacillus sp were significantly (P<0.05) different among the groups. Conversely, Salmonella sp and Micrococcus luteus counts were not significantly (P>0.05) different among the treatments. It was concluded that CPMCM can be used to replace maize up to 30 % in the diet of weaned pigs without causing any deleterious effect on the performance of animals.